P98 Is pooling of self-taken specimens an effective and acceptable method of testing for sexually transmitted infections in MSMs?. (23rd May 2012) - Sultan, B J; Fish, R; Carrick, G; Gilson, R; Robinson, A; Mercey, D; White, J; Benn, P
Abstract : Background: APTIMA Combo 2 (AC2) performs well for the detection of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) from extra-genital sites in high prevalence groups such as men who have sex with men (MSM), but testing three samples (pharynx, urethra and rectum) is a significant cost pressure for services. Aims: To determine the; (1) Performance of AC2 to detect CT and NG from a pooled specimen: self-taken pharyngeal and rectal samples added to first-void urine (PS) compared with standard of care testing from individual sites (SOC). (2) Acceptability of pooling among MSM. Methods: MSM (symptomatic or contacts of CT/NG) attending two London sexual health services were recruited. Information about demographics, sexual behaviour, symptoms, signs and acceptability of pooling was collected. PS and SOC sampling order was randomised and results compared. Results: Of the planned 1400 MSM, 99 (53 HIV+) have been recruited. Two equivocal results were excluded from analysis. Some of the questionnaire data were missing. 80%(73/91) were symptomatic and 60% (57/96) reported unprotected anal sex in the last month. The prevalence of CT and/or NG infection was 35% (95% CI 26% to 45%), CT alone 14% (95% CI 8% to 23%) and NG alone 21% (95% CI 13% to 30%). The sensitivity and specificity of PS vs SOC to detect CT/NG is 88% (95% CI 72% to 96%) and 100% (95% CI 93% to 100%), respectively (abstract P98 table 1 ). PS failed to detect four NG cases (3 pharynx, 1 rectum). MSM reported confidence (n=74, 86%) and willingness (n=75, 88%) to take their own samples (see abstract P98 table 1 ). Discussion: Pooling specimens in MSM offers the potential for significant savings and improved access to testing. Missed infections may be due to sampling error or low organism load. The evaluation of this strategy continues.